2013
DOI: 10.4049/jimmunol.1300348
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cells Carrying TCR Recognizing Epidermal Autoantigen Induce Psoriasis-like Skin Inflammation

Abstract: Psoriasis is considered a Th17-type autoimmune skin inflammatory disease; however, involvement of an autoantigen-specific TCR has not been established. In this study, we show that psoriasis-like skin inflammation can be induced by autoreactive Th17 cells. We previously developed the desmoglein 3–specific TCR-transgenic (Dsg3H1) mouse, in which CD4+ T cells recognize physiological epidermal autoantigen. T cells from Dsg3H1 mice were polarized into Th17 cells in vitro and then adoptively transferred into Rag2−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…This strengthens the concept that not only ACD, but also psoriasis is driven primarily by immune responses to specific stimuli [6]. Recent evidence argue for epidermal antigens such as desmoglein 3 as potential trigger of a psoriatic T cell response [26]. While in line with the literature, in nickel-induced ACD a Th2 and a cytotoxic immune response mediated by CD8+ T cells was more frequent than in psoriasis [18], psoriasis lesions were infiltrated by a higher number of IL-17+ immune cells [27].…”
Section: Discussionsupporting
confidence: 75%
“…This strengthens the concept that not only ACD, but also psoriasis is driven primarily by immune responses to specific stimuli [6]. Recent evidence argue for epidermal antigens such as desmoglein 3 as potential trigger of a psoriatic T cell response [26]. While in line with the literature, in nickel-induced ACD a Th2 and a cytotoxic immune response mediated by CD8+ T cells was more frequent than in psoriasis [18], psoriasis lesions were infiltrated by a higher number of IL-17+ immune cells [27].…”
Section: Discussionsupporting
confidence: 75%
“…This mechanism may also play a role in other autoimmune diseases because high levels of IL-17 similar to that detected in our patients have been described in SLE, 24,28 RA, 29,30 and psoriasis. [31][32][33] Moreover, decreased Fas function has been also detected in patients displaying autoimmune diseases different from ALPS and DALD. [34][35][36] The antiapoptotic effect of IL-17s may be partly due to modulation of cFLIP expression since exposure to IL-17A substantially upmodulated cFLIP S and downmodulated cFLIP L in Fas-stimulated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, anti-TNF is a mainstay of therapy for psoriasis, and anti-IL-17A therapy was recently approved as a first-line systemic treatment (10,11). While the involvement of peptide-reactive T cells has been well defined (12)(13)(14)(15), the role of lipid-reactive T cells in psoriasis remains largely unknown. Since psoriasis and cardiovascular disease are correlated with hyperlipidemia and recent studies have identified CD1-restricted self-lipid-reactive T cells in the blood or skin of humans (16)(17)(18)(19), we developed a new mouse model for the study of human CD1-restricted T cell responses to self-lipids in vivo.…”
Section: Introductionmentioning
confidence: 99%